A study on Oral Manifestations in type II diabetes mellitus patients - Kumar, Harish; Nishat, Roquaiya; Desai, Anupama (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes, a heterogeneous group of chronic metabolic disorders, is characterized by abnormal high levels of blood glucose, resulting either due to deficiency of insulin secretion or due to resistance to the action of insulin, or both. Chronic hyperglycemia can result in a wide variety of complications, including oral complications.To assess the type and frequency of oral lesions occurring in patients with type 2 diabetes and correlate them with the control of diabetes.The present study included a total of 161 known diabetic patients attending the clinics of private practitioners in the past two years. A clinical data performa was designed to obtain demographic data, medical and dental history. Data on the duration of disease, type of diabetes, HbA1C values, any major complications, were retrieved from the medical records. An accurate examination of the mouth, analysis of the salivary, dental, periodontal conditions and of the prosthesis used was performed. All the data obtained was analyzed using descriptive analysis. The study comprised of 92 females and 69 males with age ranging from 25 to 86 years. Majority of the patients showed periodontal manifestations followed by tooth loss, dental caries and xerostomia. Most of the patients showing severe periodontal manifestations and evidence of candidiasis had HbA1C values ≥8.5% i.e.poorly controlled diabetes level.Prevalence of oral complications was significantly higher in diabetic patients, which can have a negative influence on their oral health, thus affecting their quality of life.